PENGEMBANGAN KOMIK DIGITAL DENGAN MODEL PROBLEM BASED LEARNING PADA MATA PELAJARAN PENDIDIKAN PANCASILA - Triana, Nur Wira (Jurnal Muara Pendidikan, 2025)
A problem-based digital comic with a learning model is being developed to help students grasp Pancasila's ideals as a unity that is mutually animated and inspired by each principle.  This research follows the 4D model (define, design, develop, and disseminate).  A questionnaire was used to collect data from SDIT Al-Farabi teachers and fifth-graders.  This research and development developed a digital comic on the relationship between Pancasila principles using Procreate version 5.3.14.  At 90% and 93.8%, the material expert validator and media expert validated the digital comic as "Very feasible".  Teachers scored 95% and students 92% on the product practicality exam, certifying it as "Very Practical". The conclusion of these results shows that digital comics with the PBL model meet the standards that are worthy of being a medium in helping the learning process, by making students problem solvers through habituation of attitudes based on Pancasila values.